DUKUNGAN TENAGA KESEHATAN TERHADAP PELAKSANAAN INISIASI MENYUSU DINI - Nidya Aryani (JKM (Jurnal Kebidanan Malahayati), 2020)
ABSTRACT Background : Early Breastfeeding Initiation (IMD) is a process of allowing a baby with its own instincts to breastfeed immediately within one hour after birth, together with contact between the baby”s skin and the mother”s skin. Support of health workers plays a role in implementation of IMD but there are still many health workers who do not support or motivate and do not facilitate the implementation of IMD during the delivery process and the commitment of health workers to implement IMD in newborns is not optimal.Purpose : To determine the relationship of health support with the implementation of IMD in maternity in the Widwife Independent Practice (PMB) Wirahayu, S.ST.       Method : This type of research used in this research is quantitative with cross sectional research design. The population of this study was all spontaneous post partum mothers treated at PMB Wirahayu, S.ST Bandar Lampung during March 2018 as many as 46 people. The research sample uses accidental sampling method where the sample taken is the entire population. Retrieval of data using a questionnaire. Data analysis using bivariate analysis with chi square.Result : The statistical test result with chi square obtained p-value = 0,000, which means ther is a relationship between the support of health workers with Early Breastfeeding Initiation (IMD).Conclusion : There is a correlation between the support of health workers for the implementation of IMD in maternity in PMB Wirahayu, S.ST in 2018 with p-value =0,000 and OR = 23,333Suggestion The Indonesian Midwives Association of Lampung Province to more often hold training or seminars related to IMD or ASI for health workers, especially midwives. Health workers are also advised to focus more on providing counseling during pregnancy examinations by advising mothers to routinely carry out examinations and be diligent in seeking information about IMD and ASI both from the KIA book or from the media. Keywords : Support of Health Workers, Early Breastfeeding Initiation, Mother of Birth ABSTRAK Latar belakang : Inisiasi Menyusu Dini (IMD) merupakan suatu proses membiarkan bayi dengan nalurinya sendiri untuk menyusu segera dalam satu jam setelah lahir, bersamaan dengan kontak antar kulit bayi dengan kulit ibu. Dukungan tenaga kesehatan berperan dalam pelaksanaan IMD namun masih banyak ditemukan tenaga kesehatan yang kurang mendukung atau memotivasi dan tidak memfasilitasi pelaksanaan IMD pada saat proses persalinan serta belum optimalnya komitmen dari tenaga kesehatan untuk menerapkan IMD pada bayi baru lahir.Tujuan penelitian : Untuk mengetahui hubungan dukungan tenaga kesehatan dengan pelaksanaan IMD pada ibu bersalin di Praktik Mandiri Bidan (PMB) Wirahayu, S.ST.Metode : Jenis penelitian yang digunakan dalam penelitian ini adalah Kuantitatif dengan desain penelitian Cross Sectional. Populasi penelitian ini adalah seluruh ibu post partum spontan di PMB Wirahayu, S.ST Bandar Lampung selama bulan Maret 2018 sebanyak 46 orang. Sampel penelitian menggunakan metode accidental sampling dimana sample yang diambil adalah seluruh populasi. Pengambilan data menggunakan kuesioner. Analisis data menggunakan analisis bivariat dengan (chi square).Hasil penelitian : Hasil uji statistik dengan chi square diperoleh p-value = 0,000 yang berarti ada hubungan dukungan tenaga kesehatan dengan Inisiasi Menyusu Dini (IMD).Kesimpulan : Ada hubungan dukungan tenaga kesehatan terhadap pelaksanaan IMD pada  ibu bersalin di PMB Wirahayu, S.ST tahun 2018 dengan p-value = 0,000 dan OR = 23,333.Saran Ikatan Bidan Indonesia Provinsi lampung untuk lebih sering mengadakan pelatihan ataupun seminar yang berkaitan dengan IMD atau ASI bagi tenaga kesehatan khususnya Bidan. Tenaga kesehatan juga disarankan  untuk lebih fokus memberikan konseling pada saat pemeriksaan kehamilan dengan menyarankan ibu untuk rutin melakukan pemeriksaan dan rajin mencari informasi mengenai IMD dan ASI baik dari buku KIA ataupun dari media. Kata Kunci : Dukungan Tenaga Kesehatan, Inisiasi Menyusu Dini, Ibu Bersalin